Effect of Long-Term Music Training on Emotion Perception From Drumming Improvisation - Di Mauro, Martina; Toffalini, Enrico; Grassi, Massimo; Petrini, Karin (Frontiers in Psychology, 2018)
Long-term music training has been shown to affect different cognitive and perceptual abilities. However, it is less well known whether it can also affect the perception of emotion from music, especially purely rhythmic music. Hence, we asked a group of 16 non-musicians, 16 musicians with no drumming experience, and 16 drummers to judge the level of expressiveness, the valence (positive and negative), and the category of emotion perceived from 96 drumming improvisation clips (audio-only, video-only, and audiovideo) that varied in several music features (e.g. musical genre, tempo, complexity, drummer’s expressiveness, and drummer’s style). Our results show that the level and type of music training influence the perceived expressiveness, valence, and emotion from solo drumming improvisation. Overall, non-musicians, non-drummer musicians, and drummers were affected differently by changes in some characteristics of the music performance, for example musicians (with and without drumming experience) gave a greater weight to the visual performance than non-musicians when giving their emotional judgments. These findings suggest that besides influencing several cognitive and perceptual abilities, music training also affects how we perceive emotion from music.